Financial Performance Analysis of PT. Bank Negara Indonesia (Persero). Tbk Using the Camel Ratio: a Case Study - Abraham Lelengboto (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze whether there is a difference in the financial performance of BNI using the CAMEL ratio. In this study the design used was descriptive statistics with the research subject, namely analysis of the financial performance of BNI bank from 2002 to 2021. The data for this study were taken from BNI bank financial reports from 2002 to 2021. The results of this study concluded that for 20 BNI 46 was able to show good financial performance. The next analysis is the need for a change in operational strategy that can increase earnings (ROA) which is higher than the industry. This study aims to analyze the financial performance of BNI 46 on the five components determined by the banking industry supervisory agency, namely the Financial Services Authority and Bank Indonesia. The five components are Capital, Assets, Management, Earnings, and Liquidity. Known as CAMEL